2016
DOI: 10.1007/s00056-015-0006-0
|View full text |Cite
|
Sign up to set email alerts
|

Vertical dimension of occlusion (VDO): cephalometric norms for a Moroccan population

Abstract: Moroccans have distinct cephalometric characteristics, which should be used as the reference in future orthodontic and prosthetic treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Occ/SN is smaller in the present study suggestive of long face in Moroccan population as they have maxilla rotating downward. 2,3,18 Occ/FH is larger in Moroccan population that can be due to Frankfurt plane inclination. GoGn/SN angle is smaller in Solan population when compared with Moroccan population showing vertical growth pattern and open bite in the Moroccans.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Occ/SN is smaller in the present study suggestive of long face in Moroccan population as they have maxilla rotating downward. 2,3,18 Occ/FH is larger in Moroccan population that can be due to Frankfurt plane inclination. GoGn/SN angle is smaller in Solan population when compared with Moroccan population showing vertical growth pattern and open bite in the Moroccans.…”
Section: Discussionmentioning
confidence: 90%
“…GoGn/SN angle is smaller in Solan population when compared with Moroccan population showing vertical growth pattern and open bite in the Moroccans. 3 However, the angle of Y-axis was increased in the Solan population when compared with the Moroccan population and it was found to be clinically significant (p < 0.05), stating more vertical growth pattern in Solan population; this is in concordance by Kharbanda et al 17 ANS-Me was found to be smaller in the Solan population when compared with the Moroccan population, reflecting that decreased lower facial heights can be attributed to the decrease in the size of mandible (Yemeni, Iraqi, Moroccan).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ousehal et al [10] in 2016 who worked on a sample of 98 students from the Faculty of Dentistry in Casablanca, meeting precise criteria of facial and occlusal normality namely skeletal class 1 with no dental overlap or overlap greater than 6mm.…”
Section: Discussion Of Materials and Methodsmentioning
confidence: 99%
“…The use of bone points by cephalometric analysis leads to increased accuracy in measurements because there is no facial or positional manipulation determining freeway space, but a functional method must also be used to improve measurements provided by lateral RX in edentulous patients. Ousehal and Sierpinska 34,35 report that cephalometric studies could lead to an adequate initial VDO, referring to Knebelman's craniometer as an adequate way to determine initial VDO that could be complemented with cephalometric studies. One of the most frequently analyzed concerns is considered by Behrensdorf 36 , who says that age and time using dentures affect VDO reestablishment and mandibular movements.…”
Section: Discussionmentioning
confidence: 99%